TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN RETRIBUSI PARKIR DI RSUD ANDI MAKKASAU PAREPARE - Ramadani, Amalia (Economos : Jurnal Ekonomi dan Bisnis, 2019)
One of the revenues from user fees is parking services that can be collected by the regions. Therefore, the purpose of this study is to conduct a study of transparency and accountability in managing parking fees at the Regional Hospital of Andi Makkasau Parepare. Where Andi Makkasau Regional Hospital is the largest PAD contributor in the City of Parepare. The research conducted is describing data or information obtained by the author from the field and then concludes in the research report made. The type of data needed is qualitative data type, namely data in the form of an explanation of the management of parking fees in the Municipality of Parepare. Management of parking fees at Andi Makkasau Regional Hospital in the City of Parepare has been carried out transparently and accountably, where the interview results are related to the number of answers stating that they have been transparent and accountable. To increase PAD City PAD City, parking officers must manage parking fees transparently in coordination with the authorized SKP, especially the distribution of parking tickets.